Communication Strategies Of The Nursing Team In The Aphasia After Cerebrovascular Accident - Regina Cláudia Silva Souza; Edna Apparecida Moura Arcuri (Revista da Escola de Enfermagem da USP, 2014)
This is an exploratory, cross-sectional study of quantitative design that aimed to identify the communication strategies used and reported by the nursing staff in the care of aphasic patients after a stroke. The techniques used were the participant observation and interviews with 27 subjects of the nursing staff of neurological units in a general hospital. The most frequently mentioned strategies were gestures (100%), verbal communication (33.3%), written communication (29.6%) and the touch (18.5 %). Among the observed strategies, the gestures reached 40.7% and the touch was present in all situations, given its instrumental character essential to care. The findings show lack of knowledge of nonverbal, proxemics , kinesics and tacesics communication. No significant differences were observed among the professional categories depending on the length of experience with respect to the strategies reported by members of the nursing staff in the care for aphasic patients.